Covid-19 and Online Music Education: A Qualitative Study on the Views of Preschool Teacher Candidates - Huseyin YILMAZ; Gul SAKARYA; Serif GAYRETLI; Onur ZAHAL (Anı Publishing, 2021)
This study aims to examine distance music education practices in the pandemic period in line with the opinions of pre-school teacher candidates. The study, in which the single case study design, one of the qualitative research approaches, was used, was carried out with 22 preschool teacher candidates studying at the Kafkas University, Turkey. The data were collected through a semi-structured interview form created by the researchers in line with expert opinions. The obtained data were collected under different themes and analyzed with content analysis. The results of the study showed that the acquisitions made by the preschool teacher candidates during distance music education were mainly based on a theoretical foundation. It was found that the greatest practical deficiency occurred in learning a musical instrument.The participants mostly expressed their views on saving time and space as the positive aspects of distance education. On the other hand, negative results were also obtained, such as the inadequacy of mutual communication in the distance education process, the lack of infrastructure in practice, and the limited course time. In future studies, it is recommended to implement synchronized applications, especially for instrument training, by supporting online materials